Preparation method and fresh-keeping application of wheat protein cross-linked edible nanocellulose coating film
Through the preparation of edible nanocellulose coating films cross-linked with wheat protein, the use of ingredients such as soybean seed nanocellulose and sodium alginate, the problems of easy dissolution and poor mechanical properties of the existing coating films are solved, and efficient fruits are achieved Fresh storage and extended shelf life.
Patent Information
- Application Number
- CN202411436845.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-13
AI Technical Summary
The existing edible coating films are prone to dissolve and rupture during fruit storage and transportation, lose their preservation effect, and have poor mechanical properties, making it difficult to effectively prevent moisture loss and microbial contamination.
The preparation method of edible nanocellulose coating film with crosslinked wheat protein is adopted, and the combination of soybean seed nanocellulose extraction and sodium alginate, gluconate-δ-lactone and other components are formed to form high mechanical strength and water resistance. and self-healing coating.
It significantly improves the mechanical strength, water resistance and self-healing properties of the coating film, extends the shelf life of the fruit, enhances the preservation effect of the fruit, avoids the dissolution and cracking of the coating film, and improves the safety and environmental protection of the packaging material. sex.
Smart Images

Figure CN119111626A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food preservation, and relates to a preparation method of an edible coating film and a preservation application thereof. Background Art
[0002] Edible coating is a green and safe fruit preservation technology that has developed rapidly in recent years and has been accepted by many consumers. Edible coating is composed of some edible biopolymers with excellent film-forming properties. It mainly forms a semi-permeable membrane with barrier properties on the surface of fruits by spraying, soaking and brushing. Edible coating can prevent mechanical damage to fruits, inhibit the respiration rate, water loss and microbial contamination of fruits, thereby extending the shelf life of fruits. However, during storage and transportation, fruits often produce a large amount of water vapor due to their own respiration, and these water vapors will dissolve the edible coating, causing the coating to lose its preservation effect. At the same time, external mechanical action will also damage the coating and lose its protective effect. Therefore, it is urgent to develop edible coatings with good mechanical strength, water resistance, water retention and self-healing properties for fruit preservation. Summary of the invention
[0003] In order to solve the problems of easy dissolution, rupture and safety of the coating, the present invention provides a method for preparing an edible nanocellulose coating cross-linked with wheat protein, which significantly improves the mechanical strength, water resistance, water retention, self-healing property, transparency and edibility of the coating, and is used for fruit preservation, significantly extending the shelf life of the fruit.
[0004] The purpose of the present invention is to implement according to the following technical solutions:
[0005] In a first aspect, the present invention provides a method for preparing an edible nanocellulose coating cross-linked with wheat protein, the method comprising the following steps:
[0006] (1) Extraction of soybean seed coat nanocellulose: Soybean seed coat is sieved and crushed, then soaked in low-temperature water, treated with high-temperature acid hydrolysis to terminate the reaction, and then treated with low-temperature ultrasound. The resulting solution is dialyzed and then precipitated with alcohol, centrifuged at low temperature, and then vacuum-frozen and dried to obtain soybean seed coat nanocellulose;
[0007] (2) Preparation of wheat protein cross-linked edible coating: Wheat protein is added to edible gum to form a mixed solution A, lactone is continuously added to the mixed solution A and stirred to form a solution B, the soybean seed coat nanocellulose obtained in step (1) is added to the solution B, stirred to form a solution C after degassing, and an edible nanocellulose coating is obtained.
[0008] In a specific embodiment, solution C can be placed in a constant temperature drying oven for drying to obtain a solid edible coating film, which can be used for morphology, structure and property determination.
[0009] In a specific embodiment, the sieving and crushing of soybean seed husks in step (1) refers to multiple sieving and crushing, specifically, first passing through a 10-20 mesh sieve to remove impurities, and then passing through a 40-80 mesh sieve by 20000-30000rpm / 100-200° rocking and grinding in a grinder for 2-5min, preferably 3-5min, and then passing through a 100-300, preferably 100-200 mesh sieve by 30000-40000rpm / 200-300° rocking and grinding in a grinder for 2-10min, preferably 5-10min.
[0010] In a specific embodiment, in step (1), the soybean seed husks are sieved and crushed and then soaked in low-temperature water, specifically, the crushed soybean seed husks are soaked in 0-4°C deionized water at a ratio of 1:5-10 (m / v) for 24-48 hours.
[0011] In a specific embodiment, the reaction is terminated after the high-temperature acid hydrolysis treatment in step (1), and the low-temperature ultrasonic treatment refers to adding 0.1-12 mol / L, preferably 0.5-2.5 mol / L hydrochloric acid to the soybean hull solution at a ratio of 1:1-5 (v / v), stirring at 40-90°C, preferably 40-60°C for 1-5h, preferably 1-4h, and then adding 1-5 times, preferably 3-5 times, deionized water to terminate the reaction, and cooling to room temperature; then placing the solution in an ultrasonic instrument at 0-4°C, 50-400W, preferably 200-400W, and ultrasonicating for 1-10min (under this condition, the ultrasonication is cyclically performed 3-5 times, each time with an interval of 5-30s), and then centrifuging the solution at 1000-4000rpm for 1-15min, preferably 2000-4000rpm for 10-15min, taking the supernatant, and adding NaOH to adjust the pH of the solution to 5-8, preferably 7-8.
[0012] In a specific embodiment, in step (1), the obtained solution is dialyzed and then precipitated with alcohol, and vacuum freeze-dried after low-temperature centrifugation, which means that the solution with adjusted pH is dialyzed (Da ≥ 8000) for 3-7 days, and deionized water is replaced every 6-18 hours; 75%-95% (v / v) ethanol solution is slowly added, and the concentrate is diluted in a ratio of 1:2-4 (v / v), stirred evenly, placed at 2-4°C for 12-48h, centrifuged at 1000-4000rpm for 5-10min, preferably at 2000-4000rpm for 5-8min, and vacuum freeze-dried for 24-48h to obtain soybean seed coat nanocellulose with a particle size of <500nm.
[0013] In a specific embodiment, the edible gum in step (2) refers to 0.01-1 g / mL sodium alginate solution, and the sodium alginate is dissolved in 4-20°C deionized water, 60-100°C, preferably 80-100°C, and stirred at 600-1500 rpm for 0.5-2h to room temperature.
[0014] In a specific embodiment, in step (2), adding wheat protein to edible gum to form a mixed solution A means adding 5-10wt% wheat gluten protein to 0.01-1g / mL sodium alginate solution, stirring at 30-60°C and 600-1500rpm for 0.5-2h, preferably 1-2h, and the resulting mixed solution is A, wherein the sodium alginate is a sodium alginate having a molar ratio of mannuronic acid to guluronic acid of 0.5-3, preferably 0.5-2, and the wheat protein is a wheat gluten protein having a ratio of gliadin to glutenin of 0.8-1.2.
[0015] In a specific embodiment, in step (2), continuing to add lactone to the mixed solution A and stirring evenly to form solution B means adding 0.5-2.5wt% glucono-δ-lactone or L-galacturonic acid-1,4-lactone to the mixed solution A in 2-6 times, stirring at 30-60°C, preferably 30-50°C, and 600-1500rpm for 0.5-2.5h each time the lactone is added, and the resulting solution is B.
[0016] In a specific embodiment, in step (2), the soybean husk nanocellulose (10-45% of the sodium alginate content, preferably 10-50%) obtained in step (1) is added to solution B, stirred evenly, and degassed to obtain solution C, which means that soybean husk nanocellulose freeze-dried powder is slowly added to solution B, stirred at 25-80°C, preferably 50-80°C, and 600-1500rpm for 0.1-0.5h (each stirring increases the temperature by 10°C, the speed by 50rpm, and the time by 0.1h), and after mixing, ultrasonic degassing is performed at 25-30°C and 100-300W for 2-5min, preferably 3-5min (repeated three times, each time with an interval of 2-5s) to obtain solution C.
[0017] In a specific embodiment, the step (2) of placing the composite solution C in a constant temperature drying oven to dry to obtain a solid edible coating film means that the solution C is dried at a temperature of 1-3 cm 2 / mL is poured into a mold and dried in a forced air drying oven at 40-60℃ for 6-14h.
[0018] The applicant adjusted the order of adding sodium alginate, wheat protein and glucono-δ-lactone (or L-galacturonic acid-1,4-lactone) and found that the edible film was not formed, indicating that the order of adding the three cannot be adjusted.
[0019] In a second aspect, the present invention protects the edible nanocellulose coating prepared by the method described above.
[0020] In a third aspect, the present invention protects the use of the edible nanocellulose coating described above in food preservation.
[0021] In a specific embodiment, the application includes the step of using a sprayer to evenly spray any of the above-mentioned solutions C on the surface of the food.
[0022] Preferably, the food is fruit.
[0023] More preferably, the fruit is banana, apple, mango and the like.
[0024] More preferably, the application comprises the following steps: using a sprayer to evenly spray the solution C onto the surface of the banana, and obtaining the banana with an edible coating after drying.
[0025] Preferably, the sprayer is a high-pressure airless atomizing sprayer, the nozzle is 1.0-2.5 mm, preferably 1.0-2.0 mm, and the spraying distance is 10-80 cm, preferably 10-30 cm.
[0026] Compared with the prior art, the present invention has the following significant advantages:
[0027] 1. The present invention extracts nanocellulose from discarded soybean husks and prepares edible coatings for preservation. The present invention not only provides a new idea for the high-value utilization of soybean husks, but also provides a new idea for the utilization of agricultural waste.
[0028] 2. Soybean seed coat nanocellulose contains a variety of hydrophilic groups (hydroxyl and carboxyl groups), which can form complexes with other polymers, enhance the cross-linking density between monomers, and thus enhance the mechanical strength of the edible coating. In addition, soybean seed coat nanocellulose has a large specific surface area, high elastic modulus, and contains a large number of anionic groups on the surface, which enhances the mechanical properties and self-healing properties of the edible coating. At the same time, it also improves the opacity of the edible coating, protects the food from ultraviolet and visible light, inhibits food lipid oxidation, color change, and loss of nutritional value, and delays food spoilage.
[0029] 3. The present invention uses sodium alginate as the film-forming matrix, wheat protein as a cross-linking agent (to increase the cross-linking degree of the monomer), glucono-δ-lactone or L-galacturonic acid-1,4-lactone as a modifier (to protonate the amino groups in the wheat protein), and soybean seed coat nanocellulose as a filler. A large number of anionic groups on the surface of sodium alginate and soybean seed coat nanocellulose cross-link with the protonated wheat protein through strong electrostatic interaction. It solves the environmental problems of poor mechanical properties, poor water resistance and water retention, low gas barrier properties, poor self-healing properties, and "white pollution" caused by discarding of traditional edible films, while also increasing the safety of packaging materials.
[0030] 4. The edible coating has a smooth surface, a tight interior, and good gas barrier properties. It has a good preservation effect on bananas and other fruits, which is beneficial to extending the shelf life of bananas.
[0031] 5. It has simple ingredients, simple preparation process, easy operation, green and environmentally friendly, strong replicability, can be used for large-scale production, and has broad application prospects in the field of food preservation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The process flow of the nanocellulose edible coating prepared by the present invention;
[0033] Figure 2 The edible nanocellulose coating prepared by the present invention;
[0034] Figure 3 This is a microstructure diagram of the nanocellulose edible coating prepared in the present invention. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below in conjunction with embodiments, but the implementation manner of the present invention should not be limited to the scope described in the embodiments.
[0036] Example 1
[0037] A method for preparing a wheat protein cross-linked edible nanocellulose coating comprises the following steps:
[0038] (1) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 20-mesh sieve to remove impurities, and then sieved through a 60-mesh sieve after being pulverized at 20,000 rpm / 150° for 5 min. Then, the sieve was passed through a 200-mesh sieve after being pulverized at 30,000 rpm / 200° for 5 min. The pulverized soybean seed coat was soaked in 4°C deionized water at a ratio of 1:5 (w / v) for 24 h. 1 mol / L hydrochloric acid was added at a ratio of 1:2 (v / v) and stirred at 50°C for 2 h. 3 times of deionized water was added to terminate the reaction and the mixture was cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 3°C and 300 W for 5 min (under this condition, the ultrasonication was repeated 3 times with an interval of 15 s each time). The solution was then centrifuged at 4000 rpm for 10 min, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 7. The pH-adjusted solution was dialyzed (Da ≥ 8000) for 3 days, with deionized water replaced every 12 h. Slowly add 95% (v / v) ethanol solution to dilute the concentrate at a ratio of 1:2 (v / v), stir evenly, place at 4°C for 24 hours, centrifuge at 2000 rpm for 8 minutes, and vacuum freeze-dry for 24 hours to obtain soybean seed coat nanocellulose with a particle size of <500 nm.
[0039] (2) Preparation of wheat protein cross-linked edible coating: Sodium alginate was dissolved in 4°C deionized water to prepare a 0.01 g / mL sodium alginate solution, and stirred at 80°C and 600 rpm for 2 h until it reached room temperature. 5% (w / w) wheat gluten protein was added to the 0.01 g / mL sodium alginate solution, and stirred at 60°C and 1000 rpm for 1 h. The resulting solution was A, wherein the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 0.5, and the wheat protein was a wheat gluten protein with a ratio of gliadin to glutenin of 0.8. 2% (w / w) glucono-δ-lactone was added to solution A in three portions, and each addition of lactone was stirred at 40°C and 1500 rpm for 0.5 h. The resulting solution was B. Soybean seed coat nanocellulose freeze-dried powder (10% of sodium alginate content) was slowly added to solution B, stirred at 70°C and 800 rpm for 0.1 h (each stirring increased the temperature by 10°C, the speed by 50 rpm, and the time by 0.1 h), and then mixed and ultrasonically degassed at 30°C and 200W for 5 min (repeated three times, with an interval of 5 s each time) to obtain solution C. Solution C was heated to 3 cm 2 / mL was poured into a mold and dried in a 60℃ forced air drying oven for 6h.
[0040] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 1.0 mm and a spraying distance of 10 cm.
[0041] Example 2
[0042] A method for preparing a wheat protein cross-linked edible nanocellulose coating comprises the following steps:
[0043] (1) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 10-mesh sieve to remove impurities, and then passed through a 70-mesh sieve after being pulverized at 30,000 rpm / 180° for 3 min. Then, it was passed through a 100-mesh sieve after being pulverized at 35,000 rpm / 270° for 8 min. The pulverized soybean seed coat was soaked in 2°C deionized water at a ratio of 1:6 (w / v) for 30 h. 0.5 mol / L hydrochloric acid was added at a ratio of 1:3 (v / v) and stirred at 60°C for 1 h. Four times of deionized water was added to terminate the reaction and the mixture was cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 4°C and 200 W for 10 min (the ultrasonication was repeated 4 times under this condition, with an interval of 20 s each time). The solution was then centrifuged at 2000 rpm for 15 min, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 7.2. The pH-adjusted solution was dialyzed (Da ≥ 8000) for 5 days, with deionized water replaced every 18 h. Slowly add 90% (v / v) ethanol solution, dilute the concentrate at a ratio of 1:3 (v / v), stir evenly, place at 2°C for 36 hours, centrifuge at 3000 rpm for 5 minutes, and vacuum freeze-dry for 30 hours to obtain soybean seed coat nanocellulose with a particle size of <500 nm.
[0044] (2) Preparation of wheat protein cross-linked edible coating: Sodium alginate was dissolved in 10°C deionized water to prepare a 0.5 g / mL sodium alginate solution, and stirred at 100°C, 1000 rpm for 1 hour until room temperature. 8% (w / w) wheat gluten protein was added to the 0.5 g / mL sodium alginate solution, and stirred at 50°C, 1500 rpm for 2 hours. The resulting solution was A, wherein the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 1.0, and the wheat protein was a wheat gluten protein with a ratio of gliadin to glutenin of 1.0. 1% (w / w) L-galacturonic acid-1,4-lactone was added to solution A in 4 portions, and each time the lactone was added, the mixture was stirred at 50°C, 1000 rpm for 1 hour. The resulting solution was B. Soybean seed coat nanocellulose freeze-dried powder (20% of sodium alginate content) was slowly added to solution B, and stirred at 80°C and 1000 rpm for 0.2 h (each stirring increased the temperature by 10°C, the speed by 50 rpm, and the time by 0.1 h), and after mixing, ultrasonic degassing was performed at 25°C and 300W for 3 min (repeated three times, with an interval of 4 s each time) to obtain solution C. Solution C was heated at 2 cm 2 / mL was poured into a mold and dried in a 55℃ forced air drying oven for 10h.
[0045] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 1.5 mm and a spraying distance of 20 cm.
[0046] Example 3
[0047] A method for preparing a wheat protein cross-linked edible nanocellulose coating comprises the following steps:
[0048] (1) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 20-mesh sieve to remove impurities, and then passed through an 80-mesh sieve after being pulverized at 25,000 rpm / 200° for 3 min. Then, it was passed through a 100-mesh sieve after being pulverized at 40,000 rpm / 300° for 6 min. The pulverized soybean seed coat was soaked in 1°C deionized water at a ratio of 1:10 (w / v) for 48 h. 2 mol / L hydrochloric acid was added at a ratio of 1:5 (v / v) and stirred at 40°C for 4 h. 5 times deionized water was added to terminate the reaction and cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 2°C and 400 W for 1 min (under this condition, the ultrasonication was repeated 3 times with an interval of 30 s each time). The solution was then centrifuged at 2500 rpm for 12 min, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 8. The pH-adjusted solution was dialyzed (Da ≥ 8000) for 7 days, with deionized water replaced every 16 h. Slowly add 75% (v / v) ethanol solution to dilute the concentrate at a ratio of 1:4 (v / v), stir evenly, place at 3°C for 48 hours, centrifuge at 4000 rpm for 6 minutes, and vacuum freeze-dry for 48 hours to obtain soybean seed coat nanocellulose with a particle size of <500 nm.
[0049] (2) Preparation of edible coating cross-linked with wheat protein: Sodium alginate was dissolved in 20°C deionized water to prepare a 1g / mL sodium alginate solution, and stirred at 90°C and 1500rpm for 0.5h until it reached room temperature. 10% (w / w) wheat gluten protein was added to the 1g / mL sodium alginate solution, and stirred at 30°C and 600rpm for 1.8h. The resulting solution was A, wherein the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 2, and the wheat protein was a wheat gluten protein with a ratio of gliadin to glutenin of 1.2. 0.5% (w / w) L-galacturonic acid-1,4-lactone was added to solution A in 5 times, and each time the lactone was added, the mixture was stirred at 30°C and 1200rpm for 2h. The resulting solution was B. Soybean seed coat nanocellulose freeze-dried powder (40% sodium alginate content) was slowly added to solution B, and stirred at 50°C and 1200 rpm for 0.5 h (each stirring increased the temperature by 10°C, the speed by 50 rpm, and the time by 0.1 h), and after mixing, ultrasonic degassing was performed at 28°C and 100W for 4 min (repeated three times, with an interval of 3 s each time) to obtain solution C. Solution C was heated to 1 cm 2 / mL was poured into the mold and dried in a 40℃ forced air drying oven for 12h.
[0050] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 2.0 mm and a spraying distance of 25 cm.
[0051] Example 4
[0052] A method for preparing a wheat protein cross-linked edible nanocellulose coating comprises the following steps:
[0053] (2) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 10-mesh sieve to remove impurities, and then passed through a 40-mesh sieve after being pulverized at 24000rpm / 100° for 4 minutes. Then, it was passed through a 200-mesh sieve after being pulverized at 33000rpm / 230° for 10 minutes. The pulverized soybean seed coat was soaked in 3°C deionized water at a ratio of 1:7 (w / v) for 36 hours. 1.5 mol / L hydrochloric acid was added at a ratio of 1:4 (v / v) and stirred at 45°C for 3 hours. 3.5 times the amount of deionized water was added to terminate the reaction, and the mixture was cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 1°C and 250W for 3 minutes (under this condition, the ultrasonication was repeated 5 times with an interval of 5 seconds each time). The solution was then centrifuged at 3000rpm for 13 minutes, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 7.4. The pH-adjusted solution was dialyzed (Da ≥ 8000) for 4 days, with deionized water replaced every 10 hours. Slowly add 80% (v / v) ethanol solution to dilute the concentrate at a ratio of 1:2.5 (v / v), stir evenly, place at 4°C for 30 hours, centrifuge at 2500 rpm for 7 minutes, and vacuum freeze-dry for 36 hours to obtain soybean seed coat nanocellulose with a particle size of <500 nm.
[0054] (2) Preparation of edible coating cross-linked with wheat protein: Sodium alginate was dissolved in 15°C deionized water to prepare a 0.25 g / mL sodium alginate solution, and stirred at 85°C and 800 rpm for 1.5 h to room temperature. 6% (w / w) wheat gluten was added to the 0.05 g / mL sodium alginate solution, and stirred at 40°C and 800 rpm for 1.5 h. The resulting solution was A, wherein the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 1.5, and the wheat protein was a wheat gluten with a ratio of gliadin to glutenin of 0.9. 1.5% (w / w) glucono-δ-lactone was added to solution A in two portions, and each addition of lactone was stirred at 35°C and 800 rpm for 1.5 h. The resulting solution was B. Soybean seed coat nanocellulose freeze-dried powder (30% of sodium alginate content) was slowly added to solution B, and stirred at 60°C and 600 rpm for 0.3 h (each stirring increased the temperature by 10°C, the speed by 50 rpm, and the time by 0.3 h), and then mixed and ultrasonically degassed at 26°C and 150W for 3.5 min (repeated three times, with an interval of 2 s each time) to obtain solution C. Solution C was heated to 1.5 cm 2 / mL was poured into the mold and dried in a 45℃ forced air drying oven for 8h.
[0055] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 1.2 mm and a spraying distance of 15 cm.
[0056] Example 5
[0057] A method for preparing a wheat protein cross-linked edible nanocellulose coating comprises the following steps:
[0058] (3) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 20-mesh sieve to remove impurities, and then sieved through a 50-mesh sieve after being pulverized at 28,000 rpm / 120° for 4 min. Then, the sieve was passed through a 200-mesh sieve after being pulverized at 38,000 rpm / 250° for 7 min. The pulverized soybean seed coat was soaked in 0°C deionized water at a ratio of 1:8 (w / v) for 42 h. 2.5 mol / L hydrochloric acid was added at a ratio of 1:1 (v / v) and stirred at 55°C for 2 h. 4.5 times deionized water was added to terminate the reaction and the mixture was cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 0°C and 350 W for 7 min (the ultrasonication was repeated 4 times under this condition, with an interval of 10 s each time). The solution was then centrifuged at 3,500 rpm for 14 min, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 7.8. The pH-adjusted solution was dialyzed (Da ≥ 8,000) for 6 days, with deionized water replaced every 6 h. Slowly add 85% (v / v) ethanol solution to dilute the concentrate at a ratio of 1:3.5 (v / v), stir evenly, place at 2°C for 12h, centrifuge at 3500rpm for 6min, and vacuum freeze-dry for 44h to obtain soybean seed coat nanocellulose with a particle size of <500nm.
[0059] (2) Preparation of edible coating cross-linked with wheat protein: Sodium alginate was dissolved in 8°C deionized water to prepare a 0.75 g / mL sodium alginate solution, and stirred at 95°C and 1200 rpm for 1.2 h to room temperature. 7% (w / w) wheat gluten was added to the 0.1 g / mL sodium alginate solution, and stirred at 55°C and 1200 rpm for 1.2 h. The resulting solution was A, wherein the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 1.2, and the wheat protein was a wheat gluten with a ratio of gliadin to glutenin of 1.1. 2.5% (w / w) glucono-δ-lactone was added to solution A in 6 portions, and each addition of lactone was stirred at 45°C and 600 rpm for 2.5 h. The resulting solution was B. Soybean seed coat nanocellulose freeze-dried powder (50% of sodium alginate content) was slowly added to solution B, and stirred at 55°C and 1500 rpm for 0.4 h (each stirring increased the temperature by 10°C, the speed by 50 rpm, and the time by 0.1 h), and then mixed and ultrasonically degassed at 27°C and 250W for 4.5 min (repeated three times, with an interval of 1 s each time) to obtain solution C. Solution C was heated to 2.5 cm 2 / mL was poured into the mold and dried in a 50℃ forced air drying oven for 14h.
[0060] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 1.8 mm and a spraying distance of 30 cm.
[0061] Comparative Example 1
[0062] A method for preparing an edible nanocellulose coating without wheat protein cross-linking comprises the following steps:
[0063] (1) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 20-mesh sieve to remove impurities, and then sieved through a 60-mesh sieve after being pulverized at 20,000 rpm / 150° for 5 min. Then, the sieve was passed through a 200-mesh sieve after being pulverized at 30,000 rpm / 200° for 5 min. The pulverized soybean seed coat was soaked in 4°C deionized water at a ratio of 1:5 (w / v) for 24 h. 1 mol / L hydrochloric acid was added at a ratio of 1:2 (v / v) and stirred at 50°C for 2 h. 3 times of deionized water was added to terminate the reaction and the mixture was cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 3°C and 300 W for 5 min (under this condition, the ultrasonication was repeated 3 times with an interval of 15 s each time). The solution was then centrifuged at 4000 rpm for 10 min, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 7. The pH-adjusted solution was dialyzed (Da ≥ 8000) for 3 days, with deionized water replaced every 12 h. Slowly add 95% (v / v) ethanol solution to dilute the concentrate at a ratio of 1:2 (v / v), stir evenly, place at 4°C for 24 hours, centrifuge at 2000 rpm for 8 minutes, and vacuum freeze-dry for 24 hours to obtain soybean seed coat nanocellulose with a particle size of <500 nm.
[0064] (2) Preparation of edible coating: Sodium alginate was dissolved in 4°C deionized water to prepare a 0.01 g / mL sodium alginate solution, and stirred at 80°C and 600 rpm for 2 h to room temperature. The resulting solution was A, in which the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 0.5. 2% (w / w) glucono-δ-lactone was added to solution A in three times, and each time the lactone was added, the mixture was stirred at 40°C and 1500 rpm for 0.5 h, and the resulting solution was B. Soybean seed coat nanocellulose freeze-dried powder (10% of the sodium alginate content) was slowly added to solution B, and stirred at 70°C and 800 rpm for 0.1 h (each time the temperature was increased by 10°C, the rotation speed was increased by 50 rpm, and the time was extended by 0.1 h). After mixing, ultrasonic degassing was performed at 30°C and 200W for 5 min (repeated three times, with an interval of 5 s each time) to obtain solution C. Solution C was placed at 3 cm 2 / mL was poured into a mold and dried in a 60℃ forced air drying oven for 6h.
[0065] (3) Spraying of edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 1.0 mm and a spraying distance of 10 cm.
[0066] Comparative Example 2
[0067] The method for preparing a wheat protein cross-linked edible nanocellulose coating without lactone modifier comprises the following steps:
[0068] (1) Soybean seed coat nanocellulose extraction: Soybean seed coat was passed through a 10-mesh sieve to remove impurities, and then passed through a 70-mesh sieve after being pulverized at 30,000 rpm / 180° for 3 min. Then, it was passed through a 100-mesh sieve after being pulverized at 35,000 rpm / 270° for 8 min. The pulverized soybean seed coat was soaked in 2°C deionized water at a ratio of 1:6 (w / v) for 30 h. 0.5 mol / L hydrochloric acid was added at a ratio of 1:3 (v / v) and stirred at 60°C for 1 h. Four times of deionized water was added to terminate the reaction and the mixture was cooled to room temperature. The solution was then placed in an ultrasonicator and ultrasonicated at 4°C and 200 W for 10 min (the ultrasonication was repeated 4 times under this condition, with an interval of 20 s each time). The solution was then centrifuged at 2000 rpm for 15 min, the supernatant was taken, and NaOH was added to adjust the pH of the solution to 7.2. The pH-adjusted solution was dialyzed (Da ≥ 8000) for 5 days, with deionized water replaced every 18 h. Slowly add 90% (v / v) ethanol solution, dilute the concentrate at a ratio of 1:3 (v / v), stir evenly, place at 2°C for 36 hours, centrifuge at 3000 rpm for 5 minutes, and vacuum freeze-dry for 24 hours to obtain soybean seed coat nanocellulose with a particle size of <500 nm.
[0069] (2) Preparation of wheat protein cross-linked edible coating: Sodium alginate was dissolved in 10°C deionized water to prepare a 0.5 g / mL sodium alginate solution, and the mixture was stirred at 100°C and 1000 rpm for 1 hour until it reached room temperature. 8% (w / w) wheat gluten protein was added to the 0.5 g / mL sodium alginate solution, and stirred at 50°C and 1500 rpm for 2 hours. The resulting solution was A, wherein the sodium alginate was a sodium alginate having a molar ratio of mannuronic acid to guluronic acid of 1.0, and the wheat protein was a wheat gluten protein having a ratio of gliadin to glutenin of 1.0. Soybean seed coat nanocellulose freeze-dried powder (20% of sodium alginate content) was slowly added to solution A, and stirred at 80°C and 1000 rpm for 0.2 h (each stirring increased the temperature by 10°C, the speed by 50 rpm, and the time by 0.1 h), and after mixing, ultrasonic degassing was performed at 25°C and 300W for 3 min (repeated three times, with an interval of 5 s each time) to obtain solution B. Solution B was heated to 2 cm 2 / mL was poured into a mold and dried in a 55℃ forced air drying oven for 10h.
[0070] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 1.5 mm and a spraying distance of 20 cm.
[0071] Comparative Example 3
[0072] The method for preparing a wheat protein cross-linked edible coating film without soybean husk nanocellulose comprises the following steps:
[0073] (1) Preparation of wheat protein cross-linked edible coating: Sodium alginate was dissolved in 20°C deionized water to prepare a 1g / mL sodium alginate solution, and stirred at 90°C and 1500rpm for 0.5h until it reached room temperature. 10% (w / w) wheat gluten protein was added to the 1g / mL sodium alginate solution, and stirred at 30°C and 600rpm for 1.8h. The resulting solution was A, wherein the sodium alginate was a sodium alginate with a molar ratio of mannuronic acid to guluronic acid of 2, and the wheat protein was a wheat gluten protein with a ratio of gliadin to glutenin of 1.2. 0.5% (w / w) L-galacturonic acid-1,4-lactone was added to solution A in 5 times, and each time the lactone was added, it was stirred at 30°C and 1500rpm for 2h. The resulting solution was B. Solution B was stirred at 1cm 2 / mL was poured into the mold and dried in a 40℃ forced air drying oven for 12h.
[0074] (3) Spraying of wheat protein cross-linked edible coating liquid: Use a high-pressure airless atomizing sprayer to evenly spray the banana surface, with a nozzle of 2.0 mm and a spraying distance of 25 cm.
[0075] Comparative Example 4
[0076] A method for preparing an emulsion type sodium alginate-tocopherol edible coating comprises the following steps:
[0077] (1) Preparation of emulsion: 1% (w / v) sodium alginate was dissolved in distilled water at 60°C, and stirred continuously for 15 min with a magnetic stirrer at 600 rpm. Emulsifier Tween 80 (1 g / 100 mL sodium alginate solution) was added, and 0.75% (w / v) α-tocopherol was added. The mixture was homogenized at 1400 rpm for 5 min. 1% (w / v) calcium chloride was added to the mixed solution of sodium alginate and 0.75% tocopherol, and the mixture was vortexed and stirred for 1 cm 2 / mL was quickly poured into the mold and dried in a 40℃ forced air drying oven for 12h.
[0078] (2) Soaking in edible coating solution: about 1000 g of bananas were immersed in 1% (w / v) calcium chloride, and then immersed in a mixed solution of sodium alginate and 0.75% tocopherol, and air-dried at room temperature.
[0079] Performance Testing
[0080] The performance tests were performed on the products obtained in Examples 1 to 5 and Comparative Examples 1 to 4.
[0081] 1. Test of water resistance and water holding capacity of edible coatings
[0082] 1) The water resistance and water retention of multifunctional sodium alginate-based edible composite coating (20 mm × 20 mm) were measured using an OCA20 video optical contact angle meter. Deionized water (3 μL) was dropped on the surface of the edible composite film using a syringe, and the contact angle was measured after stabilization for 20 seconds, and the water phase contact angle was recorded.
[0083] 2. Mechanical properties and self-healing test of edible coating
[0084] 1) The mechanical properties of multifunctional sodium alginate-based edible composite coating (30 mm × 10 mm × 2 mm) were tested using a TA-XT plus SMS instrument. The elongation at break and tensile strength of the edible composite film were tested using a tensile probe. Parameters: pre-test speed of 1 mm / s, test speed of 3 mm / s, post-test speed of 2 mm / s, distance of 30 mm, and trigger force of 10.0 g.
[0085] 2) The self-healing process of the multifunctional sodium alginate-based edible composite coating was observed using a domestic DMEX30 optical microscope. The composite film was cut with a scalpel, 50 μm of deionized water was added to the scratch, and the self-healing degree of the edible composite film was observed after 60 seconds.
[0086] 3. Edible coating gas permeability test
[0087] 1) The water vapor permeability of the multifunctional sodium alginate-based edible composite coating was evaluated according to the ASTM standard with some modifications. The edible composite film (4 cm × 4 cm) was simply wrapped around the mouth of a glass bottle containing 8 g of silica gel and sealed tightly. All glass vials were placed in a constant temperature and humidity incubator (25°C, 50% RH) and weighed every 12 h until 72 h. Finally, the water vapor permeability of each composite film was calculated as follows:
[0088]
[0089] 2) Place corn oil (40 mL) in a test cup with a diameter of 5 cm and a height of 8 cm and seal it with an edible composite film with a diameter of 12 cm. Place the test cup in a constant temperature and humidity chamber (25° C., 75% RH) for 7 days. The lipid peroxide value (mmol / kg) is calculated according to the Chinese national standard (GB / T 5538-2005) and used to evaluate the oxygen permeability.
[0090] 3) Test the carbon dioxide transmission rate of the multifunctional sodium alginate-based edible composite coating. Briefly, a saturated potassium solution (20 mL) was placed in a test cup with a diameter of 5 cm and a height of 8 cm, and sealed with an edible composite film with a diameter of 12 cm. The test cup was placed in a constant temperature and humidity chamber (25°C, 75% RH) for 48 h and weighed. The calculation formula for carbon dioxide transmission rate is as follows:
[0091]
[0092] 4. Edible coating transmittance test
[0093] The transmittance of the multifunctional sodium alginate-based edible composite coating was determined by a UV-visible spectrophotometer with a scanning range of 200-800 nm and a scanning speed of 20 nm / s.
[0094] Table 1 Main performance analysis table
[0095]
[0096]
[0097] Results Analysis
[0098] The results are shown in Table 1. The mechanical properties and water resistance of the edible film prepared in Comparative Example 3 are relatively low. The edible film prepared in Comparative Example 4 has low mechanical strength, poor healing ability, low light transmittance, and the surface of the edible film is yellow, which lacks practicality. The properties of Comparative Examples 1 and 2 are between the above two comparative examples and do not show superior performance. The difference between Examples 1 to 5 and Comparative Examples 1 to 4 is that cellulose is nano-sized and surface-modified, which increases the specific surface area of cellulose and gives cellulose new functional groups (carboxyl groups). In Examples 1 to 5, hydrogen bonds, ester bonds and strong electrostatic interactions are formed between soybean seed coat nanocellulose and sodium alginate, which increases the degree of cross-linking between monomers and forms a stable cross-linked structure, thereby improving the tensile strength of the edible film. Moreover, glucono-δ-lactone can protonate the amino group of wheat protein, making wheat protein positively charged. Wheat protein acts as a lubricant between sodium alginate and soybean seed coat nanocellulose chains, increasing the crosslinking density between sodium alginate and soybean seed coat nanocellulose, thereby improving the elongation at break of the composite coating. At the same time, the edible film has high water resistance and water holding capacity, low gas permeability, and high transparency, which helps to prevent and control water evaporation, weaken fruit aerobic respiration, reduce nutrient consumption, and directly observe the appearance of food. In Example 3, the addition amount of soybean seed coat nanocellulose in the edible film is the highest, and the performance in all aspects is the most significant. Compared with Comparative Example 4, the elongation at break, tensile strength, light transmittance and healing ability of the coating of Example 3 are increased by 2585%, 122%, 675% and 233% respectively.
[0099] Freshness test
[0100] 1. Banana weight test: At a fixed time every day, bananas are weighed using a 1 / 10,000 electronic scale. The weight loss rate of bananas is calculated using the following formula:
[0101]
[0102] 2. Banana hardness test: The hardness of banana pulp was measured using a TA-XT plus SMS instrument with the following parameters: pre-test speed of 2 mm / s, test speed of 2 mm / s, post-test speed of 2 mm / s, and a trigger force of 5.0 g.
[0103] 3. The pH and acidity of banana pulp were measured using a pH-3C precision pH meter. Briefly, 20 g of bananas of different storage times were chopped and added to 50 mL of deionized water and homogenized.
[0104] 4. Test of total phenol content in banana: The total phenol content in banana pulp was determined by the Folin-Ciocalteu method with gallic acid as the standard. Briefly, the banana pulp was crushed into deionized water, dissolved and filtered, and the filtrate (1 mL) was mixed with Folin-Ciocalteu solution (0.5 mL) and sodium carbonate solution (10%, 1 mL), and incubated at 35°C with shaking for 30 min. The absorbance of the mixed solution at 750 nm was measured.
[0105] 5. Banana browning index test: 2 g of banana pulp was crushed into 80% ethanol solution, mixed evenly, ultrasonicated (200 W) for 1 h, centrifuged at 4000 rpm for 30 min, filtered, the supernatant was taken, and the absorbance at 420 nm was tested.
[0106]
[0107] After the edible coatings of Examples 1-5 form a thin film on the surface of bananas, the film delays the weight loss and softening of bananas, inhibits the oxidation of total phenols, delays the browning of banana peel and the ripening of fruits, and can extend the shelf life of bananas to 9 days. The effect is better than that of Comparative Examples 1 to 4, among which Example 3 has the most obvious effect.
[0108] The description of the above embodiments is to further illustrate the present invention, but should not be understood as limiting the scope of the present invention. For those skilled in the art, equivalent modifications or replacements can be made to part or all of the technical solutions. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing an edible nanocellulose coating cross-linked with wheat protein, characterized in that: The method comprises the following steps: (1) Extraction of soybean seed coat nanocellulose: Soybean seed coat is sieved and crushed, then soaked in low-temperature water, treated with high-temperature acid hydrolysis to terminate the reaction, and then treated with low-temperature ultrasound. The resulting solution is dialyzed and then precipitated with alcohol, centrifuged at low temperature, and then vacuum-frozen and dried to obtain soybean seed coat nanocellulose; (2) Preparation of wheat protein cross-linked edible coating: Wheat protein is added to edible gum to form a mixed solution A, lactone is continuously added to the mixed solution A and stirred to form a solution B, the soybean seed coat nanocellulose obtained in step (1) is added to the solution B, stirred to form a solution C after degassing, and the solution C is dried to obtain a solid edible coating.
2. The method for preparing the wheat protein cross-linked edible nanocellulose coating according to claim 1, characterized in that: In the step (1), the soybean husks are sieved and crushed by first passing through a 10-20 mesh sieve to remove impurities, then passing through a 40-80 mesh sieve after being swung and polished by a grinder at 20000-30000rpm / 100-200° for 2-5min, and then passing through a 100-300 mesh sieve after being swung and polished by a grinder at 30000-40000rpm / 200-300° for 2-10min. Preferably, the soaking in low-temperature water in step (1) means soaking the crushed soybean seed husks in 0-4° C. deionized water at a ratio of 1:5-10 m / v for 24-48 hours.
3. The method for preparing the wheat protein cross-linked edible nanocellulose coating according to claim 1, characterized in that: In the step (1), the reaction is terminated after the high-temperature acid hydrolysis treatment, and the low-temperature ultrasonic treatment refers to adding 1:1-5 v / v, 0.1-12 mol / L hydrochloric acid to the soybean husk solution and stirring at 50-90° C. for 1-5 hours, then adding 1-5 times deionized water to terminate the reaction, and cooling to room temperature; then placing the solution in an ultrasonic instrument at 0-4° C. and 50-400W for 1-10 minutes, and then centrifuging the solution at 1000-4000 rpm for 1-15 minutes, taking the supernatant, and adding NaOH to adjust the solution pH to 5-8; Preferably, in step (1), dialyzing the obtained solution and then precipitating it with alcohol, centrifuging it at low temperature and then vacuum freeze-drying it means that the solution with adjusted pH is dialyzed for 3-7 days, and deionized water is replaced every 6-18 hours; 75%-95% v / v ethanol solution is slowly added, and the concentrate is diluted in a ratio of 1:2-4v / v, stirred evenly, placed at 2-4°C for 12-48h, centrifuged at 1000-4000rpm for 5-10min, and vacuum freeze-dried for 24-48h to obtain soybean seed coat nanocellulose with a particle size of <500nm.
4. The method for preparing the wheat protein cross-linked edible nanocellulose coating according to claim 1, characterized in that: The edible glue in step (2) refers to 0.01-1 g / mL sodium alginate solution, which is dissolved in 4-20° C. deionized water, stirred at 60-100° C. and 600-1500 rpm for 0.5-2 h until the temperature reaches room temperature; Preferably, in step (2), adding wheat protein to edible gum to form a mixed solution A means adding 5-10wt% wheat gluten protein to 0.01-1g / mL sodium alginate solution, stirring at 30-60°C and 600-1500rpm for 0.5-2h, and the resulting solution is A, wherein the sodium alginate is a sodium alginate having a molar ratio of mannuronic acid to guluronic acid of 0.5-3, and the wheat protein is a wheat gluten protein having a ratio of gliadin to glutenin of 0.8-1.
2.
5. The method for preparing the wheat protein cross-linked edible nanocellulose coating according to claim 1, characterized in that: In step (2), the step of continuously adding lactone to the mixed solution A and stirring evenly to form solution B means adding 0.5-2.5 wt % of glucono-δ-lactone or L-galacturonic acid-1,4-lactone to the mixed solution A in 2-6 portions, stirring at 30-60° C. and 600-1500 rpm for 0.5-2.5 h each time the lactone is added, and the resulting solution is solution B.
6. The method for preparing the wheat protein cross-linked edible nanocellulose coating according to claim 1, characterized in that: In step (2), the soybean husk nanocellulose obtained in step (1) is added to solution B, stirred evenly, and degassed to obtain solution C, which means that soybean husk nanocellulose freeze-dried powder is slowly added to solution B, stirred at 25-80° C. and 600-1500 rpm for 0.1-0.5, and after mixing, ultrasonically degassed at 25-30° C. and 100-300 W for 2-5 min to obtain solution C; Preferably, the soybean husk nanocellulose accounts for 10-45% of the sodium alginate content.
7. The method for preparing the wheat protein cross-linked edible nanocellulose coating according to claim 1, characterized in that: In step (2), the composite solution C is placed in a constant temperature drying oven to dry to obtain a solid edible coating film, which means that the solution C is dried at a temperature of 1-3 cm 2 / mL is poured into a mold and dried in a forced air drying oven at 40-60℃ for 6-12h.
8. The edible nanocellulose coating prepared by the method described in any one of claims 1 to 7.
9. Use of the edible nanocellulose coating according to claim 8 in food preservation; Preferably, the application comprises the step of uniformly spraying the solution C described in any one of claims 1 to 7 on the surface of the food using a sprayer; Preferably, the food is fruit; More preferably, the fruit is banana, apple or mango.
10. The use according to claim 9, characterized in that: The application comprises the following steps: using a sprayer to evenly spray solution C onto the surface of bananas, and after drying, bananas with edible coatings are obtained; Preferably, the sprayer is a high-pressure airless atomizing sprayer with a nozzle of 1.0-2.5 mm and a spraying distance of 10-80 cm.
Citation Information
Cited By
Lipid-solubly modified proteins, methods for their production and uses thereof
CN122749723A
